DEVELOPMENT OF A MULTIMODAL TOOL TO SUPPORT TEACHING OF ROOT CANAL ANATOMY OF PRIMARY MOLARS: AN OBSERVATIONAL CROSS-SECTIONAL STUDY TO EVALUATE THE ACCEPTANCE OF UNDERGRADUATE STUDENTS: Received: 22nd December 2022 Revised: 04th June 2024 Accepted: 24th April 2024 - Maysa Lannes Duarte; Mariana Coutinho Sancas; Renata Perez Vianna Silva; Aline de Almeida Neves; Laura Guimarães Primo (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The study developed a multimodal imaging tool to support the teaching of root canal anatomy of primary molars and evaluated its acceptance by dentistry students. A cross-sectional study was developed and divided into two parts: creation of a video and elaboration of an electronic questionnaire to assess acceptance. Both were pre-tested for content and comprehension. Undergraduate dental students who were attending or had already attended a Pediatric Dentistry course were eligible. Data were collected from for two months and analyzed descriptively and comparatively (Wilcoxon test). A total of 135 students, mostly female (79.26%), from last or before last year (54.81%) at private institutions (86.67%), with an average age of 25.36±6.46 years old. Most of them (78.52%) were attending the Pediatric Dentistry course in the current semester, with online classes, synchronously (57.04%). Almost half (50.37%) thought they had reasonable knowledge about the anatomy of primary teeth before watching the video, and 59.26% did not seek extra information about the subject. Self-knowledge on the topic improved after watching the video (p<0.01). From those who answered the questionnaire completely (115), 99.13% considered the video relevant and 100% thought the information was clear. Video was well accepted by students while being important to help increase their knowledge.